2019
DOI: 10.1101/601385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prior physical synchrony enhances rapport and inter-brain synchronization during subsequent educational communication

Abstract: Physical synchrony has been suggested to have positive effects on not only concurrent but also subsequent communication, but the underlying neural processes are unclear.Using functional near-infrared spectroscopy (fNIRS) hyperscanning, we tested the effects of preceding physical synchrony on subsequent dyadic teaching-learning communication. Thirty-two pairs of participants performed two experimental sessions.In each session, they underwent a rhythmic arm movement block with synchronous or asynchronous conditi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 91 publications
(113 reference statements)
1
15
0
1
Order By: Relevance
“…Nevertheless, Liu et al (2019) found IBS in the left prefrontal cortex (PFC) and not in the right TPJ (rTPJ) when comparing face-to-face and computer-mediated communication conditions. In a context of participants engaged in prior physical synchrony, Nozawa et al (2019) reported that IBS in the PFC region between teacher and learner was enhanced and positively associated with teacher learner rapport. Finally, neural alignment regarding alpha-band wave activity was detected for listeners in the frontal region and speakers in the central region and with respect to the theta band in the temporal region for the listener and frontal region for the speaker (Pérez et al, 2017).…”
Section: Search Methods and Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, Liu et al (2019) found IBS in the left prefrontal cortex (PFC) and not in the right TPJ (rTPJ) when comparing face-to-face and computer-mediated communication conditions. In a context of participants engaged in prior physical synchrony, Nozawa et al (2019) reported that IBS in the PFC region between teacher and learner was enhanced and positively associated with teacher learner rapport. Finally, neural alignment regarding alpha-band wave activity was detected for listeners in the frontal region and speakers in the central region and with respect to the theta band in the temporal region for the listener and frontal region for the speaker (Pérez et al, 2017).…”
Section: Search Methods and Inclusion Criteriamentioning
confidence: 99%
“…In addition to determining alignment following WTC, Pan et al (2020) Of ten studies assessing the brain activity involved in knowledge sharing, three were carried out using EEG, while the rest were performed with fNIRS ( Table 1). The cortical regions activated and exhibiting IBS while sharing knowledge include frontal (Holper et al, 2013;Liu et al, 2019;Nozawa et al, 2019;Pan et al, 2018), temporal-parietal (Zheng et al, 2018), and frontal and temporal-parietal (Bevilacqua et al, 2019;Dikker et al, 2017;Pan et al, 2020;Pérez et al, 2017) areas. In a classroom study by Dikker et al (2017), IBS emerged from averaged neural activity over a variety of cortical regions between students which was greatest during interactive class discussion compared to lecture, reading, and video conditions.…”
Section: Search Methods and Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1 , the distribution of hyperscan conditions dedicated to each of the nine categories defined by our framework is highly unequal. Over half of all reported hyperscan conditions (57.8%, N = 87) were conducted when the interacting dyad were in the same room without any means of digital interaction (i.e., Analog ToI) (Funane et al, 2011 ; Holper et al, 2012 , 2013 ; Jiang et al, 2012 , 2015 ; Osaka et al, 2014 , 2015 ; Duan et al, 2015 ; Liu N et al, 2016 ; Nozawa et al, 2016 , 2019 ; Hirsch et al, 2017 , 2018 ; Ikeda et al, 2017 ; Zhang et al, 2017a , b ; Zhao et al, 2017 ; Dai et al, 2018a , b ; Fishburn et al, 2018 ; Pan et al, 2018 , 2020a ; Xue et al, 2018 ; Zhang Y et al, 2018 ; Lu et al, 2019 , 2020 ; Mayseless et al, 2019 ; Niu et al, 2019 ; Vanzella et al, 2019 ; Noah et al, 2020 ), while (42.4%, N = 64) included some element of technology (e.g., playing a computer game) while participants were in the same room (Cui et al, 2012 ; Dommer et al, 2012 ; Duan et al, 2013 ; Cheng et al, 2015 , 2019 ; Liu T et al, 2015 , 2016 , 2017 ; Baker et al, 2016 ; Tang et al, 2016 ; Balconi and Vanutelli, 2017a , b ; Hu et al, 2017 ; Pan et al, 2017 , 2020b ; Piva et al, 2017 ; Takeuchi et al, 2017 ; Fishburn et al, 2018 ; Zhang M et al, 2018 ; Zheng et al, 2018 , 2020 ; Balconi et al, 2019 ; Liu et al, 2019 ; Nozawa et al, 2019 ; Sarinasadat et al, 2019a …”
Section: Deriving An Fnirs Hyperscanning Frameworkmentioning
confidence: 99%
“…However, the classification of the comparisons reported were limited to Analog vs. Mixed and Inter-ToI comparisons. The studies comprised comparisons between Mixed ToI/Joint goal-driven ToC and Mixed ToI/Mixed ToC ( N = 5) (Cui et al, 2012 ; Cheng et al, 2015 ; Liu T et al, 2015 , 2016 , 2017 ), Analog ToI/Mixed ToC and Analog ToI/Joint goal-driven ToC ( N = 7) (Jiang et al, 2012 ; Holper et al, 2013 ; Osaka et al, 2014 , 2015 ; Hirsch et al, 2018 ; Niu et al, 2019 ; Vanzella et al, 2019 ), Analog ToI/Joint open-ended ToC and Analog ToI/Joint goal-driven ToC ( N = 3) (Liu N et al, 2016 ; Ikeda et al, 2017 ; Zhang Y et al, 2018 ), and Analog ToI/Mixed ToC and Mixed ToI/Joint goal-driven ToC ( N = 2) (Nozawa et al, 2019 ; Noah et al, 2020 ). Two studies included three cross-condition comparisons, including comparisons between Analog ToI/Mixed ToC, Analog ToI/Joint goal-driven ToC, and Mixed ToI/Joint open-ended ToC ( N = 1) (Fishburn et al, 2018 ), as well as between Analog ToI/Joint goal-driven ToC, Analog ToI/Joint open-ended ToC, and Mixed ToI/Joint goal-driven ToC ( N = 1) (Yang et al, 2020 ).…”
Section: Deriving An Fnirs Hyperscanning Frameworkmentioning
confidence: 99%